PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA FILT THE FLAP BOOK TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SDN 76 TAROWANG KEC. GALESONG SELATAN KAB. TAKALAR - Ikhwanul Ikhsan; Aliem Bahri; Anin Asnidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem in this study is the low learning outcomes of Indonesian language participants taught by the provision of media variations by teachers. The study aims to determine the influence of the Discovery Learning learning model Assisted by Filt The Flap Book media on the learning outcomes of Indonesian language in class IV SDN 76 Tarowang. With the research problem